2010
DOI: 10.1016/j.bmcl.2009.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and screening of a CaaL peptide library versus FTase reveals a surprising number of substrates

Abstract: Proteins bearing a CaaL sequence are typically geranylgeranylated to enable their proper localization and function. We found that many of the dansyl-GCaaL peptides representing mammalian CaaL proteins can be farnesylated by FTase. This result may have important implications for prenylated protein biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
(36 reference statements)
3
26
0
Order By: Relevance
“…In this study, sequences for which product conversion was detected by HPLC were labeled as ‘true’ substrates, while sequences for which no conversion was detected were labeled as ‘false’ substrates [23]. Using the threshold of -0.4 results in predictions with 87.5% TPR and 17.5% FPR, consistent with the performance on other peptide libraries (Figure 2C).…”
Section: Resultssupporting
confidence: 68%
“…In this study, sequences for which product conversion was detected by HPLC were labeled as ‘true’ substrates, while sequences for which no conversion was detected were labeled as ‘false’ substrates [23]. Using the threshold of -0.4 results in predictions with 87.5% TPR and 17.5% FPR, consistent with the performance on other peptide libraries (Figure 2C).…”
Section: Resultssupporting
confidence: 68%
“…Of course, several other proteins can become isoprenylated, for example, Rheb proteins, nuclear lamins, Rac and Cdc42. 12,13 Finally, we investigated whether the observed findings also hold true for primary human AML cells. Heterogeneity in the cytotoxic effects of simvastatin, as well as differences in the degree of rescue by mevalonate, GGPP and FPP, were found in primary AML cells (Supplementary Table S1).…”
Section: Letters To the Editormentioning
confidence: 99%
“…Using this approach, Krzysiak and colleagues demonstrated that FTase readily catalyzes farnesylation of a large number of peptides terminating in Leu (-CaaL), contrary to the CaaX paradigm which describes these as canonical GGTase-I substrate sequences [4]. This result expands the pool of FTase substrates and demonstrates additional cross-reactivity with GGTase-I.…”
Section: Substrate Identificationmentioning
confidence: 99%